Protein Produced by Bacillus subtilis ATCC11774 after Inducing with Allium sativum Extract - Hanina Mohd Noor; Salina Mat Radzi; Maryam Mohamed Rehan; Hairul Shahril Muhamad (International Institute of Chemical, Biological & Environmental Engineering, 2024)
Non-Indexed Publication